2013
DOI: 10.5194/acp-13-2923-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the South American regional smoke plume: aerosol optical depth variability and surface shortwave flux perturbation

Abstract: Intra-seasonal variability of smoke aerosol optical depth (AOD) and downwelling solar irradiance at the surface during the 2002 biomass burning season in South America was modeled using the Coupled Chemistry-Aerosol-Tracers Transport model with the Brazilian developments on the Regional Atmospheric Modeling System (CCATT-BRAMS). Measurements of total and fine mode fraction (FMF) AOD from the AErosol RObotic NETwork (AERONET) and solar irradiance at the surface from the Solar Radiation Network (SolRad-NET) were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 47 publications
4
43
0
4
Order By: Relevance
“…Consistent with previous studies (Freitas et al, 2005(Freitas et al, , 2017Longo et al, 2010Longo et al, , 2013Rosário et al, 2013;Moreira et al, 2013), BRAMS performed well while modeling the meteorology and aerosol biomass burning emission, transport, and removal processes in Amazonia, which has resulted in accurate simulation of the major features of AOD variability associated with the regional biomass burning plume over South America. The model results for surface temperature, rainfall, and AOD were once again in agreement with observations for the 2010 dry season case study, representing the main characteristics of the spatial distribution and the diurnal cycle of temperature and precipitation.…”
Section: Conclusion and Final Remarkssupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with previous studies (Freitas et al, 2005(Freitas et al, , 2017Longo et al, 2010Longo et al, , 2013Rosário et al, 2013;Moreira et al, 2013), BRAMS performed well while modeling the meteorology and aerosol biomass burning emission, transport, and removal processes in Amazonia, which has resulted in accurate simulation of the major features of AOD variability associated with the regional biomass burning plume over South America. The model results for surface temperature, rainfall, and AOD were once again in agreement with observations for the 2010 dry season case study, representing the main characteristics of the spatial distribution and the diurnal cycle of temperature and precipitation.…”
Section: Conclusion and Final Remarkssupporting
confidence: 67%
“…The radiation scheme is a modified version of the Community Aerosol and Radiation Model for Atmospheres (CARMA; Toon et al, 1988), which includes the aerosolradiation interaction with feedback to the model heating rates Rosário et al, 2013). In addition, we included in CARMA a parameterization to calculate the diffuse fraction of solar irradiance specific to biomass burning aerosols in Amazonia.…”
Section: Biosphere Model: the Joint Uk Land Environment Simulator (Jumentioning
confidence: 99%
“…Prins et al (1998) found that the majority of the biomass fires observed in South America between 0 to 40°S and 35 to 75°W occurred in August and September, and recent data reported 444,059 fire foci nationwide in August andSeptember 2014 (INPE, 2015). The onset of the rainy season in October diminishes the fire foci (58,290 in the period December 2014-January 2015) and the increase of the aerosol optical depth is more related to smoke bursts due to local emissions (Rosário et al, 2013). We chose two subperiods within UTF dry and UTF wet , and combined location of fire foci in South America (INPE, 2015) with 120-h air mass backtrajectories calculated with HYSPLIT (Hybrid Single-Particle Lagrangian Integrated Trajectory) model (Draxler and Rolph, 2011) arriving in Londrina at 500 m above terrain level with 1-hour interval.…”
Section: Bc Concentrations In Different Seasons: Contributions Of Locmentioning
confidence: 99%
“…As mentioned above, the incoming solar radiation was dimmed compared to the days before and after this BB event. Furthermore, the cloud fraction decreased, which might result from stabilizing the atmosphere due to increased absorption of solar radiation in and above the boundary layer (Koren et al, 2004;Rosenfeld et al, 2008;Rosario et al, 2013). A detailed investigation of the direct radiative forcing and the modification of cloud properties by aerosol particles in the Amazon rain forest are clearly beyond the 15 scope of this study.…”
mentioning
confidence: 99%